Sustainable financial investments : maximizing corporate profits and long-term economic value creation - Bolton, Brian (Professor) (Diversity, leadership and responsibility series., 2015)
"Is it possible for an investment to be good for a firm's profitability without also being good for the environment, employees, or community? Author Brian Bolton connects these seemingly disparate ideas and shows how to incorporate economic costs, benefits, cash flows and risks into the evaluation of any type of investment, with particular focus on those investments that are driven by environmental, human, and social considerations. Bolton mixes economic and finance rigor with applied case studies and examples throughout the book to see how the real world fits into the economic and financial analysis structure. By the end of the book readers will have an appreciation for at least two important issues: (1) analysis of all investments do follow a similar process; and, (2) the specific assumptions and variables that are necessary to include in the analysis of sustainability-related investments."--